Clinical features of de novo CD25-positive follicular lymphoma. Issue 2 (February 2014) - Fujiwara, Shin-ichiro; Muroi, Kazuo; Tatara, Raine; Matsuyama, Tomohiro; Ohmine, Ken; Suzuki, Takahiro; Mori, Masaki; Nagai, Tadashi; Tanaka, Akira; Ozawa, Keiya
Abstract CD25 expression in follicular lymphoma (FL) has not yet been investigated. Eighty-five patients with newly diagnosed FL were retrospectively evaluated. On two-color flow cytometric analysis, CD25 was detected on CD19 + and CD20 + lymphoma cells. CD25 expression in FL tended to be higher than in reactive lymphadenopathy, but was lower than in diffuse large B-cell lymphoma. Patients with CD25 + FL (n = 12) showed clinical features of elevated soluble interleukin-2 receptor (IL-2R) levels, B symptoms and an advanced age compared with CD25 − FL (n = 73). The overall response rate (ORR), progression-free survival (PFS) and overall survival (OS) in patients with CD25 + FL were significantly inferior to those with CD25 − FL (ORR, 60 vs. 93%; 2-year PFS, 32 vs. 80.3%; 6-year OS, 47.4 vs. 85.9%, respectively). Multivariate analysis demonstrated that CD25 positivity is an independent prognostic factor for PFS and OS in FL. CD25 + FL may constitute a distinct subgroup associated with aggressiveness and an inferior prognosis.